implementasi Manajemen Holistik Dalam Pendidikan Islam di Pondok Pesantren Al Hamidiyah Depok - Jerry Hendrajaya; Nanat Fatah Natsir; Mohamad Jaenudin (Reslaj : Religion Education Social Laa Roiba Journal, 2019)
This study aims to determine the holistic education at Al Hamidiyah Islamic boarding school in Depok, the existence of Holistic education management at the Al Hamidiyah Islamic boarding school in Depok, which includes planning, organizing, implementing, and monitoring aspects, and to determine the efforts to improve Holistic management in Islamic Education in Islamic Boarding Schools Al Hamidiyah. Ideally Al Hamidiyah Islamic Boarding School has set the foundation for the implementation of Holistic education. From the management aspect, Holistic education management functions have also been established and implemented. Therefore a research with a qualitative approach was conducted. The research technique was carried out by interview, observation and document review techniques. The results showed that the Al Hamidiyah Sawangan Islamic Boarding School in Depok had organized a Holistic education as seen in its vision, mission, and special objectives and various activities. Such education is inseparable from the history of its founder and the environmental conditions that surround it, both at its inception, the history of its development, to the present condition. Holistic education management implemented or organized by the Al Hamidiyah Islamic Boarding School in Depok has used the stages of planning, organizing, implementing, and supervising in the education process in general and learning in particular at various types and levels of education at the Al Hamidiyah Islamic Boarding School. There are still a number of deficiencies in the implementation of Holistic education in Al Hamidiyah Islamic Boarding School, in addition to a number of advantages possessed. Among the shortcomings are superior human resources, incomplete facilities and infrastructure, and the use of information technology that has not been maximized. Keywords: Management, Islamic Education, Islamic Boarding Schools, Holistic.